Community-associated methicillin-resistant Staphylococcus aureus in non-outbreak skin infections - Bonesso, Mariana Favero [UNESP]; Marques, Silvio Alencar [UNESP]; Camargo, Carlos Henrique [UNESP]; Castelo Branco Fortaleza, Carlos Magno [UNESP]; Ribeiro de Souza da Cunha, Maria de Lourdes [UNESP] (Soc Brasileira Microbiologia, 2014)
The aim of this study was to determine the prevalence of Staphylococcus aureus and risk factors for the acquisition of MRSA (Methicillin Resistant Staphylococcus aureus) as the main cause of skin and soft tissue infections. S. aureus were characterized for the presence of PVL, TSST-1 and mecA genes. SCCmec typing was carried out in mecA positive strains and PFGE was performed only in these strains. During the study period, 127 outpatients attending a dermatology clinical the Botucatu Medical School, a regional tertiary hospital in Botucatu, Sao Paulo, Brazil, were diagnosed with active skin infections. A total 66 (56.9%) S. aureus strains were isolated. The methicillin resistance gene mecA was detected in seven (10.6%) S. aureus strains. The SCCmec types detected in the seven mecA-positive S. aureus strains were type Ia in one, type II in three, and type IV in three. The PVL gene was detected in 10 (15.1%) in sensitive strains. Pulsed field gel electrophoresis revealed non-clonal diversity among the isolates. The risk factors associated with MRSA acquisition in this study were previous ciprofloxacin use and working in a healthcare environment. The risk factors indicate plausible routes of CA-MRSA transmission among the subjects studied.
Keywords: Staphylococcus aureus; resistance; skin infections; virulence; epidemiology